P085 Chronic recurrent multifocal osteomyelitis: about 2 cases. (11th November 2021) - Miladi, Saoussen; Makhlouf, Yasmine; Fazaa, Alia; Sellami, Mariem; Ouenniche, Kmar; Souabni, Leila; Kassab, Selma; Chekili, Selma; Ben Abdelghani, Kawther; Laatar, Ahmed
Abstract: Background: Chronic recurrent multifocal osteomyelitis (CRMO) also known as aseptic osteomyelitis is a rare auto-inflammatory disease with an incidence estimated at 4/100 000 population [1]. The aim of our work was to report two cases of CRMO that illustrate challenges in the diagnosis of this rare disease. Method: We report the case of two patients diagnosed with CRMO. Clinical, biological and radiological data as well as disease outcomes were described. We also collected data about treatment modalities. Results: Two patients aged of 7 and 10 years respectively, without any notable pathological history, presented recurrent episodes multifocal painful swelling of limbs. In the first case, the symptoms concerned the left ankle and knee as well as the left hip, all associated with lameness and an altered general condition, with neither fever nor skin manifestations. In the second case, the swelling involved the right shoulder, right hip and the left ankle. There was no elevated CRP or ESR in any of patients. Immunological status (RF, anti-CCP, AAN) as well as the HLA-B27 antigen test were negative. In the first patient, standard radiographs showed lytic lesions of the proximal metaphysis of the tibia, the greater trochanter and the left lateral malleolus. MRI of the pelvis, knee, and sternum of the first patient revealed edematous involvement of the left greater trochanter, the right ilium, the proximal metaphyseal region of the tibia and the right edge of the sternum, whereas in the second patient, a whole-body MRI showed inflammatory signs over the left greater trochanter, the insertion of the gluteus medius and obturator externus, right trochanteric bursitis and oedema of the entire right ilium. In the first patient, bone scintigraphy showed intense uptake of radioisotopes in the left ilium, the 7 th right costo-vertebral junction, the trochanteric mass, the upper end of the tibia and the lower end of the left fibula. Bone biopsy showed bone remodeling in both cases without evidence of infection or tumor. The diagnosis of CRMO was retained, supported by the prompt response to NSAIDs and short-term corticosteroid therapy. However, the second patient presented, 8 years later, pain in the sterno-clavicular joint as well as the right hip. A relapse of the disease was confirmed by MRI. Therapeutic escalation with zoledronic acid 0.025 mg/kg intravenous infusion every six months allowed the resolution of the symptoms. Conclusion: These observations illustrated a rare disorder in children, characterized by lytic lesions predominantly in the metaphysis of long bones. Bone scintigraphy allowed an early assessment of disease extension and histological examination ruled out a malignant tumor and an infection. The first-line treatment is anti-inflammatory drugs. In case of failure, bisphosphonates seem to be effective.